Fenomenologi Mental Accounting Dalam Pengelolaan Keuangan Rumah Tangga Pada Masyarakat Kota Sampit - Wukuf Dilvan Rafa; Anggun Permata Husda; Syarbini Ikhsan (Owner : Riset dan Jurnal Akuntansi, 2026)
This exploratory qualitative research using a phenomenological approach aims to uncover the role of accounting implementation and the contribution of mental accounting in household financial management practices in the community of Kota Sampit. The phenomenon of financial failure in households, which often triggers high divorce rates due to economic motives, is a crucial background for this study. Data were collected through in-depth interviews with five married informants with varying occupational backgrounds and income sources. Data analysis was conducted using non-statistical methods including data reduction, data presentation, and conclusion drawing. The results show that the application of accounting principles in the form of consistent cash flow recording has a direct positive impact on economic growth and family stability. Families that make financial decisions based on financial records have a clear planning direction, experience an improved quality of life, and are able to anticipate unnecessary consumptive expenses. Conversely, financial management that relies purely on intuition without record-keeping is prone to wasteful behavior and dependence on digital debt (paylater). Furthermore, the construction of mental accounting, manifested through the classification of budget items and psychological flexibility in revising expenses, has proven to act as an effective early warning system. Amid economic uncertainty caused by logistical constraints and global inflationary pressures, mental accounting skills are a lifeline for people's purchasing power and maintain household harmony. Self-control, practical accounting literacy, and transparency between husband and wife are key factors in creating strong family financial resilience.